2012
DOI: 10.1145/2362402.2362406
|View full text |Cite
|
Sign up to set email alerts
|

Excavation-parallel laser scanning of a medieval cesspit in the archaeological zone cologne, germany

Abstract: During the construction of an underground museum in the historic city center of Cologne, Germany, large parts of the Roman and medieval city are being excavated. The newly excavated remains as well as remains of the Roman city, which had already been excavated in 1954, exhibit structural damages. While at first deficiencies in the construction were assumed to be the cause of the damages, in 2003 a seismogenic origin was suggested. To further test this hypothesis of seismically induced slope movements and other… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 50 publications
1
9
0
Order By: Relevance
“…This setting gave the audience a breathtaking view rising to the 80 m high cliff and the upper castle. The structure is typical for Roman theaters of that period in Asia Minor and largely follows the common rules given later in the first century BC by Marcus Vitruvius Pollio [15]. The auditorium, cavea, covers more than a half circle so that the side walls, analemma, form an obtuse angle (Figs.…”
Section: Field Survey Of the Theatermentioning
confidence: 55%
See 1 more Smart Citation
“…This setting gave the audience a breathtaking view rising to the 80 m high cliff and the upper castle. The structure is typical for Roman theaters of that period in Asia Minor and largely follows the common rules given later in the first century BC by Marcus Vitruvius Pollio [15]. The auditorium, cavea, covers more than a half circle so that the side walls, analemma, form an obtuse angle (Figs.…”
Section: Field Survey Of the Theatermentioning
confidence: 55%
“…In order to obtain a clear view of the seating rows, the cavea was cleared of most of the vegetation growing between the seating rows, particularly in the southern section. Previous scanning campaigns [15] showed that the use of targets or spheres did not significantly improve the overall registration error when combining point clouds compared to the target-less registration technique and application of least square algorithm. Based on this experience, no targets were used in the survey of the theatre.…”
Section: Field Survey Of the Theatermentioning
confidence: 94%
“…We used the laser scanning technique to create a comprehensive virtual model (CVM) of the remains of the whole excavation complex (Schreiber et al 2009(Schreiber et al , 2012Schreiber and Hinzen 2011). In full resolution, the CVM contains 2.3 billion georeferenced 3D points.…”
Section: D Laser Scan Modelmentioning
confidence: 99%
“…In full resolution, the CVM contains 2.3 billion georeferenced 3D points. Special challenges included the repeated scanning of the 8.3 m deep cesspit during its excavation (Schreiber et al 2012) and the 13 m deep Roman well (Fleischer et al 2010). The CVM enhances visualization and quantification of the damage found in the study area, which were previously described (i.e., Doppelfeld 1956;Precht 1973;Hinzen and Schütte 2003), as well as damage described here for the first time in their archeoseismological context.…”
Section: D Laser Scan Modelmentioning
confidence: 99%
See 1 more Smart Citation